The use of SNPs in characterizing oysters genomes and their resistance to pathogens - Lapegue, Sylvie; Heurtebise, Serge; Harrang, Estelle; Morga, Benjamin; Flahauw, Emilie; Sauvage, Christopher; Boudry, Pierre (Aquaculture Europe - The annual meeting of the European Aquaculture Society, Porto, Portugal October 5-8, 2010, 2010)
During the last five years, a great effort has been made to develop genomic tools in oyster species all over the world. In Europe, the Pacific cupped oyster, Crassostrea gigas, and the European flat oyster, Ostrea edulis received a special attention as they are the key species for local aquaculture. In particular, the Pacific oyster is a marine bivalve of major economical and ecological importance worldwide. Better knowledge of its physiology and its genetics contributes to optimize its aquaculture production using selective breeding or to understand its invasive behavior in some coastal areas. Current international developments of genomic resources include EST databases, BAC libraries, genome mapping and sequencing. The Genoscope (Evry, France) and the Max Plank Institute (Berlin, Germany) have notably performed sequencing projects, as part of the collaborative work developed within the EU funded projects (‘Marine Genomics Europe’: www.marine-genomics-europe.org and ‘Aquafirst’: http://aquafirst.vitamib.com). This led to the release of a novel dedicated EST database (www.sigenae.org.aquafirst), allowing the development of additional markers (microsatellites and SNPs), and transcriptome studies. SNPs were notably detected in candidate ESTs revealed as differentially expressed between lines selected for high or low survival to summer mortality by microarray studies. A very high level of polymorphism was observed. Moreover, a consensus linkage map was built using SNPs and microsatellites markers and allowed detecting quantitative trait loci for better survival to summer mortality and Ostreid Herpes virus type 1 load, a virus involved in summer mortality. This kind of approach is of particular interest as the function of candidate genes can be indirectly investigated by performing association studies between polymorphic candidate genes and phenotypic traits. Furthermore, at the population level, genome scans are performed to reveal the footprints of natural selection by identifying loci showing higher genetic ...